Nutrition in IBD patient's. What are the prospects? - Tomasello, Giovanni; Abruzzo, Alida; Sinagra, Emanuele; Damiani, Provvidenza; Damiani, Francesco; Traina, Giovanna; Campanella, Claudia; Rappa, Francesca; Marino Gammazza, Antonella; Noto, Marcello; Palumbo, Vincenzo Davide; Damiano, Giuseppe; et al. (Progress in Nutrition, 2015)
Inflammatory bowel disease (IBD) is a chronic disorder characterized by a relapsing-remitting course, which alternates between active and quiescent states, ultimately impairing a patients’ quality of life.  The two main types of IBD are Crohn’s disease (CD) and ulcerative colitis (UC). In physiological conditions the gut is costantly exposed to various antigens, commensal microflora and pathogens and the inflammatory response is finely balanced. It is thought that a vast number of environmental risk factors may be implicated in the development of IBD, including smoking, dietary factors, psychological stress, use of non-steroidal anti-inflammatory drugs and oral contraceptives, appendectomy, breastfeeding, as well as infections. Nutritional support, as a primary therapy, has a crucial role in the management of patients with IBD. The gut microbiota is clearly manipulated by dietary components such as n-3 polyunsaturated fatty acids (n-3 PUFA) and coniugated linoleic acid (CLA) which favorably reduce endotoxin load via shifts in the composition and metabolic activity of the microbial community. In particular, the beneficial effect of n-3 PUFAs and fermentable fiber, during the remission/quiescent phase of both CD and UC is highlighted. In fact, PUFAs are associated with a less grade of inflammation since they are metabolized to 3-series prostaglandins and thromboxanes and 5-series leukotrienes and, in addition, exert antiinflammatory effects when compared with their n-6 PUFA counterparts. In similar action to dietary n-3 PUFA, coniugated linoleic acid (CLA) have been reported to ameliorate intestinal inflammation in animal models of IBD. Currently is still unclear the role of the fibers in  helping the remission of the disease. Data about the consumption of fiber are controversial. On one hand, dietary fibers can act as effective prebiotics by altering the intestinal microbial composition and promoting the growth of beneficial bacterial communities within the large intestine.  On the other hand,  fibers can promote diarrhea, pain and gas aggravating the clinical state. We suggest that the consumption of fermentable fibers may have a good impact on patients’ health.